The KNOTTIN website and database: a new information system dedicated to the knottin scaffold - Gelly, Jean-Christophe (Oxford University Press, 2004)
The KNOTTIN website and database organize information about knottins or inhibitor cystine knots, small disulfide-rich proteins with a knotted topology. Thanks to their small size and high stability, knottins provide appealing scaffolds for protein engineering and drug design. Static pages present the main historical and recent results about knottin discoveries, sequences, structures, folding, functions, applications and bibliography. Database searches provide dynamically generated tabular reports or sequence alignments for knottin three-dimensional structures or sequences. BLAST/HMM searches are also available. A simple nomenclature, based on loop lengths between cysteines, is proposed and is complemented by a uniform numbering scheme. This standardization is applied to all knottin structures in the database, facilitating comparisons. Renumbered and structurally fitted knottin PDB files are available for download. The standardized numbering is used for automatic drawing of two-dimensional Colliers de Perles. The KNOTTIN website and database are available at http://knottin.cbs.cnrs.fr and http://knottin.com.